The princess in black and the mermaid princess ebook - Hale, Shannon (Princess in Black, 2022)
There's trouble under the sea! Can the Princess in Black and her new mermaid friend put a stop to a big blue kraken's shenanigans? The Princess in Black and her friends are enjoying a day of sun and sea on Princess Sneezewort's royal boat when a real, live mermaid princess emerges from the waves! Eeeeeee! Princess Posy needs their help protecting her very cute sea goats from being eaten by a very greedy kraken. But the princesses and the Goat Avenger quickly realize that fighting underwater can be tough for land dwellers, and only the mermaid Princess Posy can save the day. Can the masked heroes help her learn that being a princess means more than just being nice—it means speaking up? An ode to using your voice (along with a kelp-tree swing or two), this newest installment in the New York Times best-selling series is a splish-splashing good time.